2012
DOI: 10.5539/ijel.v2n1p162
|View full text |Cite
|
Sign up to set email alerts
|

An Intercultural Communication Study of Chinese and Malaysian University Students’ Refusal to Invitation

Abstract: One of the challenges brought about by intercultural communication is the cross-cultural understanding of whatis meant by what is said in another culture. Performing a given communicative act in a different cultural background than the speakers' own requires taking into consideration several issues in order not to be perceived as impolite, rude, or even offensive in the host community.The present study aims to investigate the pragmatic behavior of refusal to invitation by Chinese international university stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
5
14
0
Order By: Relevance
“…In Malaysia, no studies have so far highlighted issues which combine both L1 interference with the speech acts of Chinese students. All studies on L1 interference in Malaysia focused either only on writing proficiencies (Siti Hamin Stapa & Mohd Mustafa Izahar 2010, Chen & Li 2016Darus & Subramanian 2009, Dipolog-Ubanan 2016, Zou 2013 or solely on speech acts (Farnia & Wu 2012;Zhao & Mohd Nor 2016). Hence, this study is significant because it combined both of these elements.…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, no studies have so far highlighted issues which combine both L1 interference with the speech acts of Chinese students. All studies on L1 interference in Malaysia focused either only on writing proficiencies (Siti Hamin Stapa & Mohd Mustafa Izahar 2010, Chen & Li 2016Darus & Subramanian 2009, Dipolog-Ubanan 2016, Zou 2013 or solely on speech acts (Farnia & Wu 2012;Zhao & Mohd Nor 2016). Hence, this study is significant because it combined both of these elements.…”
Section: Introductionmentioning
confidence: 99%
“…A refusal can be accepted or appropriate for a certain nationality or culture, but not for other nationalities or cultures. Refusals require not only long sequences of negotiation and cooperative achievements, but also "face-saving maneuvers to accommodate the noncompliant nature of the act" (Gass andHouck, 1999 in Farnia &Wu, 2012). Therefore, people commonly negotiate the refusal through any supportive statement which is possible to lessen the offensive or threats and possible to maintain other' negative face.…”
Section: Introductionmentioning
confidence: 99%
“…According to Athieh and Yassin (2011), there have been a lot of studies on the speech acts of request, compliment, apology and complaint in the sociocultural pragmatics, but not on refusal. Refusals have not much studied but are being paid increasing attention to (Beebe, et.al.,1990;Bardovi-Hartford, 1990;Liao and Breshnahan, 1996;Blum-Kulka and Olshtain 1984;Gass 1999;Takahashi and Beebe 1987;Nelson andCason 2002 in Farnia &Wu, 2012). Moreover, from those researches which examine refusal strategies, it is found that only few researches which investigate the use of refusal strategies by non-native speaker of English.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The employment of reasons, apologies and alternatives as the three salient strategies used by the MSE and the NSE were in line with findings of studies by Beebe et.al. (1990), Farnia and Wu (2012), and Sattar and Farnia (2014).…”
Section: Figure 2 Mse Vs Nse Direct Strategies When Refusing High Stamentioning
confidence: 99%